Acesso ao Programa de Aquisição de Alimentos (PAA) e segurança alimentar em assentamentos da região centro norte de São Paulo - Bocca, Matheus Ferreira [UNESP]; Camargo, Regina Aparecida Leite de [UNESP]; Matos, Jean Marcos Soares de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The article presents the results of a research carried on in settlement areas in the northern and central regions of São Paulo state, with the application of 142 semi structured questionnaires to estimate the access of settlers to the Food Acquisition Program (PAA) and its impact in the food security of families. It was demonstrated that in spite of the potential of this program, the access remains below what could be expected.

O trabalho apresenta os resultados de pesquisa realizada em assentamentos rurais na região centro norte de São Paulo, com aplicação de 142 questionários semi-estruturados, para verificar o acesso dos assentados ao Programa de Aquisição de Alimentos (PAA) e seu impacto na segurança alimentar das famílias. Demonstrou-se que apesar do potencial do programa, o acesso fica aquém do que se poderia esperar.
Keywords: Family farming; Public policies; Institutional markets; Agricultura familiar; Políticas públicas; Mercados institucionais